(untitled) (Fiep Bulletin - online, 2014)
The aim of this study was to evaluate the effect of Mulligan techniques and physical therapy in post operative Bankart shoulder injury surgery patient. The subject presented reduction of the active range of movement, mainly of flexors and abductors of shoulder, reduction considerable of force of abductors and external rotators, beyond reduction of muscular mass according to perimeter analysis. The appointments with the patients were realized two times a week, with 50 minutes and after 10 sessions, the reevaluation of the condition was established. After the application of the Mulligan techniques and physical therapy, had an increment of the range of movement of flexors (70° for 118º) and of abductors (60º for 110°), as well as of the force of abductors (3 for 4) and external rotators (3 for 4). In the reevaluation perimeter, it was observed concomitantly, an increase of the muscular mass. The physical therapy allied Mulligan techniques had collaborated for the improvement of the patient having become more functional the left superior member proving the necessity of the treatment conservative after surgical intervention.